From palliative to curative intent: PET/CT findings in the light of breast cancer intrinsic subgroup. Issue 6 (December 2019) - Brunet, Maxime; Cazeau, Anne-Laure; Ben Rejeb, Houda; Catena, Vittorio; Grellety, Thomas
Purpose: Among breast cancer subgroups, Luminal A is the subgroup with the best prognosis. We report the case of a young woman presenting with a localized luminal A breast cancer with a suspicious liver lesion on initial positron emission tomography (PET)/computed tomography (CT) scan staging. Case description: A 31-year-old woman presented with localized breast cancer accessible to curative treatment. However, PET/CT staging revealed an increase of focal activity in the liver, suspicious of a secondary malignant localization, changing the care towards palliative intent. Discrepancy between breast cancer luminal A subtype and the liver lesion led to further investigations (contrast ultrasound, magnetic resonance imaging, and biopsy), excluding a malignant process, and were in favor of toxic hepatitis, probably secondary to herbal tea consumption. Conclusions: Questioning PET/CT findings in light of the cancer subtype enabled us to rectify the diagnosis and allow this patient to be treated with curative intent.